Game theoretical inference of human behavior in social networks - Nicolò Pagan (Nature Portfolio, 2019)
Based on a strategic network formation model, the authors develop game-theoretical and statistical methods to infer individuals’ incentives in complex social networks, and validate their findings in real-world, historical data sets.